Comparison of circulation patterns of mumps virus in the Netherlands and Spain (2015–2020) - Gavilán, Ana M.; van de Nes-Reijnen, Linda; Castellanos, Ana; Woudenberg, Tom; López-Perea, Noemí; Masa-Calles, Josefa; Echevarría, Juan E.; Fernández-García, Aurora; Bodewes, Rogier (Frontiers in Microbiology, 2023)
Background Mumps is a viral infection mainly characterized by inflammation of the parotid glands. Despite of vaccination programs, infections among fully vaccinated populations were reported. The World Health Organization (WHO) recommends molecular surveillance of mumps based on sequencing of the small hydrophobic (SH) gene. The use of hypervariable non-coding regions (NCR) as additional molecular markers was proposed in multiple studies. Circulation of mumps virus (MuV) genotypes and variants in different European countries were described in the literature. From 2010 to 2020, mumps outbreaks caused by genotype G were described. However, this issue has not been analyzed from a wider geographical perspective. In the present study, sequence data from MuV detected in Spain and in The Netherlands during a period of 5 years (2015- March 2020) were analyzed to gain insights in the spatiotemporal spread of MuV at a larger geographical scale than in previous local studies. Methods A total of 1,121 SH and 262 NCR between the Matrix and Fusion protein genes (MF-NCR) sequences from both countries were included in this study. Analysis of SH revealed 106 different haplotypes (set of identical sequences). Results Of them, seven showing extensive circulation were considered variants. All seven were detected in both countries in coincident temporal periods. A single MF-NCR haplotype was detected in 156 sequences (59.3% of total), and was shared by five of the seven SH variants, as well as three minor MF-NCR haplotypes. All SH variants and MF-NCR haplotypes shared by both countries were detected first in Spain. Discussion Our results suggest a transmission way from south to north Europe. The higher incidence rate of mumps in Spain in spite of similar immunization coverage in both countries, could be associated with higher risk of MuV exportation. In conclusion, the present study provided novel insights into the circulation of MuV variants and haplotypes beyond the borders of single countries. In fact, the use of MF-NCR molecular tool allowed to reveal MuV transmission flows between The Netherlands and Spain. Similar studies including other (European) countries are needed to provide a broader view of the data presented in this study.